2018
DOI: 10.1186/s13012-017-0707-4
|View full text |Cite
|
Sign up to set email alerts
|

Navigating the sustainability landscape: a systematic review of sustainability approaches in healthcare

Abstract: BackgroundImprovement initiatives offer a valuable mechanism for delivering and testing innovations in healthcare settings. Many of these initiatives deliver meaningful and necessary changes to patient care and outcomes. However, many improvement initiatives fail to sustain to a point where their full benefits can be realised. This has led many researchers and healthcare practitioners to develop frameworks, models and tools to support and monitor sustainability. This work aimed to identify what approaches are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
444
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 266 publications
(464 citation statements)
references
References 87 publications
(151 reference statements)
19
444
1
Order By: Relevance
“…We found they define sustainability in terms of three concepts: continued capacity to deliver the innovation, continued delivery of the innovation, and continued receipt of benefits. These concepts align well with the academic literature on this topic [18,[43][44][45]. At the same time, participants provided a nuanced view of these concepts, with both continued delivery and continued benefits only relevant under certain conditions.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…We found they define sustainability in terms of three concepts: continued capacity to deliver the innovation, continued delivery of the innovation, and continued receipt of benefits. These concepts align well with the academic literature on this topic [18,[43][44][45]. At the same time, participants provided a nuanced view of these concepts, with both continued delivery and continued benefits only relevant under certain conditions.…”
Section: Discussionsupporting
confidence: 57%
“…Several authors have recently shown the most common definition of sustainability is the continuation or maintenance of an innovation or its activities [18,43]. Interestingly, the most prevalent element of sustainability discussed in this study was continued capacity, which was not integrated in Moore et al's recent comprehensive definition [18].…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…This construct, as presented, is intended to capture perceptions of sustainability at a health systems level throughout and after implementation, and not sustained behavior at an individual level. For studies focused solely on studying determinants or outcomes of sustainability, we suggest that researchers utilize models and frameworks focused explicitly on exploring the dynamics of sustainability [53,54].…”
Section: Description Of Newly Proposed Constructsmentioning
confidence: 99%
“…Patient and public involvement (PPI) initiatives often try to amplify patient voices in healthcare settings (for example in the UK, NHS Shared Decision Making, 2017; National Institute for Health and Care Excellence [NICE], 2016), including through co-production, in which patients and the public work with healthcare providers to improve services . Achieving and sustaining healthcare co-production is of interest to healthcare policy makers, clinicians and researchers (Gruen et al, 2008;Lennox, Maher, & Reed, 2018), and has the potential to generate 'meaningful ways of shaping and taking part in health care' (Filipe et al, 2017, p. 2). This might take the form of shared decision making with patients (NHS, 2017), or developing patient-centred services in hospitals and clinics (Robert et al, 2015).…”
Section: Introductionmentioning
confidence: 99%